Facile synthesis of 5-Isopropyl-2,3-dimethylbenzene-1,4-diol by Friedel-Crafts and Determination of Partition Coefficient in n- Octanol/Water - Siti Mariyah Ulfa; Alma Miranda; Fath Dwisari; Mohammad Farid Rahman (Jurnal Kimia Sains dan Aplikasi, 2022)
The wide therapeutic effect of quinone-based drugs has received considerable interest for a long time. In this research, Friedel-Crafts performed a facile synthesis of quinone derivatives using the mixture of Brønsted acid. Reflux of 2,3-dimethylhydroquinone (1), isopropanol, glacial acetic acid, and H2SO4 for 15 minutes gave yellow oil product of 5-isopropyl-2,3-dimethylbenzene-1,4-diol (2) as a major product. Characterization using Nuclear Magnetic Resonance (NMR) revealed the methine proton splitting for isopropyl at δ 3.13 ppm, which has a cross-coupling with aromatic carbon at δ 119.6 ppm suggested the substitution of a proton on quinone ring with isopropyl group. Analysis Fourier Transform Infra-Red (FT-IR) showed the broad spectrum of –OH, the vibration of CH sp3, and isopropyl groups. The minor products identified as 5-isopropyl-2,3-dimethylcyclohexa-2,5-diene-1,4-dione (3), 5-isopropyl-2,3-dimethyl-1,4 phenylene diacetate (4), and 2,3-dimethylbenzene-5,6-isopropyl-1,4-diol (5) confirmed from 2D HETCOR and MS analysis. The partition coefficient (log P) of compound 2 showed a higher solubility by 1.9-fold compared to hydroquinone 1. It is suggested that an additional methyl group increased the partition into the organic phase.